Poor governance and massive unemployment in Nigeria: as causes of brain drain in the Buhari administration (2015-2020) - Benedict Ogheneakpoje Ighoshemu; Ufuoma Benson Ogidiagba (Insights into Regional Development, 2022)
Like other African countries of the developing world, Nigeria underperforms due to a lack of state capacity to deal with the present-day complexities of governance, thereby leading to poor governance, massive unemployment, and brain drain in the Buhari administration. Poor governance is the absence of good governance. Close observation of governance in Nigeria indicates a poor attempt at democratic consideration and unstable politics thereby leading to a battered economy, impoverishment of citizens, corruption, mismanagement of public funds, infrastructure decay leading to massive unemployment which results in human capital flight, a barrier to Nigeria’s quest for consolidating democracy, As a result of visionless leaders, selfish, nepotic, mediocrates, tribalistic and opportunist in the political space of the country. This paper examines the electionary campaign promises of the Buhari administration on security for all citizens, bumper economy, and anti-corruption, with the analysis of secondary data, it examines the relationship between poor governance, massive unemployment, and brain drain in Nigeria from 2015 to 2020, adopting the relative deprivation of frustration-aggression theory to x-ray the concepts of poor governance and massive unemployment, resulting to human capital flight. This study has identified poor governance and massive unemployment leading to brain drain in this administration and made valuable recommendations.